Electrolysis of molten nitrates on graphite electrodes : Kinetics of the anodic reaction - Arvia, Alejandro Jorge (1966)
The anodic reaction occurring during the electrolysis of molten nitrates on graphite electrodes at temperatures from 230 to 320°C has been studied. The overall reaction is 2N<msubsup is="true">O3−</msubsup>+C=CO2+2NO2+2e Current/voltage curves in the range 0·5–200 mA/cm2 fit a Tafel line with a slope 2RT/F. The decay of anodic overvoltage is logarithmic with time in a region beyond 10 ms, depending on the current density. The decay process indicates a high pseudo-capacitance, which decreases as the anodic overvoltage increases. Results obtained from steady current/voltage curves, decay and build-up of the anodic overvoltage, and the temperature effect can be explained with the aid of known results on the kinetics of thermal oxidation of graphite and on the anodic reaction taking place on platinum electrodes. At high overvoltage a high degree of oxidation caused by the NO 3 intermediate is achieved, and the rate-determining step of the anodic reaction is then C(O)+N<msubsup is="true">O3−</msubsup>→NO2+CO2+e A stable residual cell formed after the interruption of electrolysis is discussed in terms of the reactions in the proposed reaction path.